2008
DOI: 10.2214/ajr.07.3773
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pelvic MRI of Anorectal Malformations

Abstract: Pelvic MRI is a valuable tool in the assessment of postoperative anorectal malformations that may necessitate additional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…The importance of siting the pulled-through rectum accurately and symmetrically in the sphincter ani at primary operation is stressed, as fecal incontinence can occur with asymmetrical placement. In contrast to many studies, 13 our finding showed 33. 3% of the patients had their pulled-through rectum sited away from the center, but analysis showed that this does not have significant impact on the outcome of the patients clinically.…”
Section: Statisticscontrasting
confidence: 99%
“…The importance of siting the pulled-through rectum accurately and symmetrically in the sphincter ani at primary operation is stressed, as fecal incontinence can occur with asymmetrical placement. In contrast to many studies, 13 our finding showed 33. 3% of the patients had their pulled-through rectum sited away from the center, but analysis showed that this does not have significant impact on the outcome of the patients clinically.…”
Section: Statisticscontrasting
confidence: 99%
“…The value is considered significant, when 'P" value is less than or equal to 0.05. (9) 4 (44.4%) 5 (55.56%) 6 (66.6%) 3 (33.33%) Absent (12) 12 0 12 0 Soiling Present (5) 0 5 (100%) 4 (80%) 1 (20%) Absent (16) 14 2 16 0 Constipation Present (7) 3 (42.86%) 4 (57.14%) 4 (57.14%) 3 (42.86%) Absent (14) 13 1 14 0 Out of these 294 patients twenty-one patients who had complained of bowel dysfunctions like soiling, constipation and bowel incontinence were included in the study. Remaining 273 cases were excluded because of normal bowel habit in 271 cases, one case having permanent faecal diversion and one case re do pull through.…”
Section: Discussionmentioning
confidence: 99%
“…MRI study is considered to provide a valuable postoperative assessment of anorectal pull-through procedures because it allows visualization of the SMC in relation to its thickness or misposition [20][21][22][23]. Advantages of MRI include an excellent inherent soft-tissue contrast enhancement, multiplanar imaging capabilities and lack of ionizing radiation; disadvantages include cost and the relatively frequent need for sedation, that can be avoided in cooperative children using fast imaging sequences.…”
Section: Discussionmentioning
confidence: 99%